ROLES OF INDIVIDUAL AND ORGANISATIONAL FACTORS IN UNETHICAL PRO-ORGANISATIONAL BEHAVIOUR - Onuoha, Chibuzor Uchenna; Bukola, Victoria Bada; Dada, Emmanuel Job (African Journal of Social and Behavioural Sciences, 2025)
Unethical pro-organisational behaviour is common in many work organisations. Few studies have examined the relations between organisational commitment and organisational identification with unethical pro-organisational behaviour among employees in the financial sector. This study investigates the role of organisational commitment and organisational identification on UPB among bank employees. The influence of education and organisational tenure on UPB was also investigated. A purposive sample of 334 bank marketing employees completed a self-administered survey on organisational commitment, organisational identification and unethical pro-organisational behaviour scales. Results showed organisational commitment to significantly and positively predict UPB (β = .40, p < .01) and contributed 24% to UPB. Organisational identification positively predicted UPB (β = .49, p < .01); it contributed 40% to the variance. In addition, education (β = .22, p < .01) and organisational tenure (β = .21, p < .01) positively contributed to UPB. These results suggest that employees who are highly committed, more educated, longer tenure and identified more closely to the organisation were more likely to engage in unethical pro-organisational behaviour. The study concludes that these individual and organisational factors positively predicted UPB among the survey participants.